2021
DOI: 10.1021/acsami.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Bond Switching in Densified Oxide Glass Enables Record-High Fracture Toughness

Abstract: Humans primarily interact with information technology through glass touch screens, and the world would indeed be unrecognizable without glass. However, the low toughness of oxide glasses continues to be their Achilles heel, limiting both future applications and the possibility to make thinner, more environmentally friendly glasses. Here, we show that with proper control of plasticity mechanisms, record-high values of fracture toughness for transparent bulk oxide glasses can be achieved. Through proper combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 49 publications
(111 reference statements)
3
23
0
Order By: Relevance
“…Notably, the fracture toughness of R = La, Sm, and Gd glass is 1.21 MPa$m 0.5 , 1.39 MPa$m 0.5 , and 1.52 MPa$m 0.5 , respectively, which is much larger than the values of current commercially available oxide glasses, such as silicates, borates, borosilicate, etc., which is reported to be lower than 1 MPa$m 0.5 (Quinna and Swab, 2013;To, 2019;Østergaard et al, 2019;Rouxel and Yoshida, 2017;Yao, 2016;Scannell et al, 2017;Vullo and Davis, 2004;Wiederhorn et al, 1974;Mezeix, 2017;Kato et al, 2010;Reddy et al, 1988), as shown in Figure 5C (areas below the gray short dash line). Currently, the highest fracture toughness of oxide glasses is reported to be 1.36 MPa m 0.5 using the single-edge pre-cracked beam method (To et al, 2021). In this work, the measured fracture toughness of R = Sm and Gd glass exhibits an almost comparable value to that of maximum record.…”
Section: Indentation Fracture Toughnessmentioning
confidence: 57%
See 4 more Smart Citations
“…Notably, the fracture toughness of R = La, Sm, and Gd glass is 1.21 MPa$m 0.5 , 1.39 MPa$m 0.5 , and 1.52 MPa$m 0.5 , respectively, which is much larger than the values of current commercially available oxide glasses, such as silicates, borates, borosilicate, etc., which is reported to be lower than 1 MPa$m 0.5 (Quinna and Swab, 2013;To, 2019;Østergaard et al, 2019;Rouxel and Yoshida, 2017;Yao, 2016;Scannell et al, 2017;Vullo and Davis, 2004;Wiederhorn et al, 1974;Mezeix, 2017;Kato et al, 2010;Reddy et al, 1988), as shown in Figure 5C (areas below the gray short dash line). Currently, the highest fracture toughness of oxide glasses is reported to be 1.36 MPa m 0.5 using the single-edge pre-cracked beam method (To et al, 2021). In this work, the measured fracture toughness of R = Sm and Gd glass exhibits an almost comparable value to that of maximum record.…”
Section: Indentation Fracture Toughnessmentioning
confidence: 57%
“…Among metallic oxides, alumina (Al 2 O 3 ) possesses the highest dissociation energy (G Al2O3 = 133.8 kJ/cm 3 ) (Makishima, 1973). Hence, it is reasonable that the glasses with high hardness, high Young's modulus, and high fracture toughness contain a great quantity of Al 2 O 3 , as reported in R 2 O 3 -Al 2 O 3 -SiO 2 glasses (R = rare earth ion, Y, or Sc) and 25Li2O-20Al2O3-55B2O 3 glass (Stevensson and Edé n, 2013;Johnson et al, 2005;Du, 2009;Inaba et al, 2000;To et al, 2021). The atomic packing density of glass increases with the coordination number of Al and decreases with the ionic volume of oxide components.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations